IMPROVING THE METHODOLOGY OF TEACHING THE KOTLIN PROGRAMMING LANGUAGE IN THE DIGITAL PEDAGOGICAL ENVIRONMENT (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
This article examines modern approaches to teaching programming within the framework of digital pedagogy. Special attention is given to the use of innovative methods, interactive technologies, and digital tools in teaching the Kotlin programming language. The article also discusses the development of algorithmic thinking, the support of independent learning, and the individualization of the educational process. The findings have practical significance for improving teaching methodologies in programming education.